The Influence of Work Motivation on Work Discipline with Job Satisfaction as an Intervening Variable for Employees of the Public Housing and Residential Areas Agency of Pekanbaru City - Fadhila, Era; Karneli, Okta; Zulkarnaini, Zulkarnaini (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This research is motivated by the importance of implementing discipline for employees and organizations. Discipline will affect work and organizational goals. Employees who do not have good discipline will result in unsatisfactory performance. discipline has an impact on performance, of course, performance is related to employee work results. Because poor work results will certainly affect the goals and even the existence of the organization. The purpose of this study was to determine and analyze the effect of work motivation on employee work discipline with job satisfaction as an intervening variable for employees of the Public Housing and Settlement Area Office of Pekanbaru City. This research method is quantitative descriptive method. Primary data is obtained directly through questionnaire results. The research sample amounted to 45 employees at the Public Housing and Settlement Area Office of Pekanbaru City. Based on the results of the research and discussion, it is concluded that: (1) work motivation, work discipline and job satisfaction of employees of the Public Housing and Settlement Area Office of Pekanbaru City are quite good. This is known from the average assessment of the three variables which are in the good enough category; (2) there is an effect of work motivation on employee work discipline; (3) there is an effect of work motivation on employee job satisfaction; (4) there is no effect of job satisfaction on employee work discipline, and; (5) there is no effect of work motivation on work discipline and job satisfaction as an intervening variable in employees of the Public Housing and Settlement Area Office of Pekanbaru City.